Evaluation of Urban Density and City Rate's Fraction and Its Effects on Increasing of Households Costs in Bojnourd City - Khodarahm Bazzi; Masoomeh Vahdaty (نشریه جغرافیا و برنامه‌ریزی, 2014)
Form and pattern of urban growth is a sign of growth and spread in variety stages and environment. This is related to social, economical, natural and human factors. This has a different pattern and had influencing to above factors, special social and economical factors. This article studies evaluation of urban growth compression and sprawl rate and its effects to increasing of household’s costs. Research method is analytic- survey and based on documents and questionnaires, data and information are consisting of indicators and criteria such as; area, population and density with use Holdren and Moran coefficient models. These data particularly urban journeys had tested to Chi Square and related to assessment of urban growth compression and sprawl rate in Bojnourd. In this research after of concluded of growth pattern and sprawl rate, studied three neighborhoods in three textures in Bojnourd. Results show urban sprawl in continuation stages with 46% in recent decade comparison to other decades. This process increased of automobile use and increased household’s economical costs.